When Idle Talk Is Idealized: Thinking with Heidegger’s Existential Analytic in a Time of Neo-Liberalism - Parker, Lana (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
Neo-liberalism’s greatest strength as an ideological force has been its ability to traverse boundaries, adapt and adopt customs and cultures, and inflect the central premise of individualism, competition, and capital creation into all manner of non-market spaces. In this article, I argue that Heidegger’s rendering of “idle talk” furnishes a useful prism for understanding the current conditions of neo-liberal influences in education. I offer two analyses of what it means to be in a time and place that is enframed by discourses of neo-liberalism and the material conditions of capitalism. First, I describe how thrown conditions in education reflect a preoccupation with a limited, neo-liberal view of what it means to care or be concerned. Second, I suggest that alternatives to neo-liberalism are less available because of impoverished conceptions of what it means to understand. I conclude with the argument that, despite the dire ontic conditions, there is much opportunity to contemplate what comes next for exploring alternative educational futures.